PROYEKSI PERGESERAN TIPE IKLIM OLDEMAN DI WILAYAH KALIMANTAN SELATAN PADA AKHIR ABAD 21 BERDASARKAN SIMULASI CORDEX-SEA - Mustika Wiratri; Emmy Sri Mahreda; Supari Supari; Badaruddin Badaruddin; Idiannor Mahyudin (Universitas Lambung Mangkurat, 2022)
Climate change has the potential to alter the spatial pattern of rainfall, which is the primary variable in climate classification. The Oldeman method is one of climate classification techniques focused on agricultural management. This study's objective is to evaluate the spatial changes of the Oldeman climatic type in South Kalimantan, Indonesia assificationt of climate change. The climate in the late 21st century is simulated using data from one of the CORDEX-SEA project's products using the RCP4.5 and RCP8.5 scenarios. The shift in climate type was assesed based on the difference of the total area covered by the Oldeman climate classification during the projection period (2071-2095) and that covered during the reference period (1981-2005). The simulation data was corrected first using the linear scaling method to reduce the bias. The skill of model in reproducing Oldeman climate type was evaluated against the surface observation data from 35 sites using the percent of correct (PoC) score method. We found that the bias correction procedure successfully reduced the bias, as evidenced by a 22% rise in the correlation value of monthly rainfall and a -79% reduction in RMSE. By the end of the 21st century, both under RCP4.5 and RCP8.5 scenarios, the South Kalimantan climate is projected to be dryer, characterized by a decrease in the area covered by wet climate types (type B) and an increase in the area covered by dry and extremely dry climate types (type D and E). We discovered that the RCP8.5 scenario could result in a more tremendous shift in climate type than the RCP4.5 scenario. This study demonstrates that climate change has the potential to result in a shift in the climate classification that must be considered in agriculture policymaking.